PRIEKIN (‘ahead’, ‘frontward’) – through space and time - Kardelis, Vytautas; Kardelytė-Grinevičienė, Daiva (Lietuvių kalba, 2016)
Based on the combination of methods of referential and cognitive semantics, this article discusses one part of the model of spatial and temporal relations, i.e. the sagittal and its realisation in discourse. The object of this study is the realisation of the sagittal by the adverbial priekin (‘ahead’, ‘frontward’) in the Vilniškiai subdialect of Northeastern Aukštaitija. This dialect features prototypical and non-prototypical uses of the adverbial priekin. In its prototypical use the adverbial refers to location in space and acquires the meaning of ‘forward to the direction of movement’, in front of oneself, ahead / frontward’) (based on LKŽ (Lietuvių kalbos žodynas [‘Dictionary of the Lithuanian Language’]). The transfer of temporal scenes into discourse makes use of the adverbial priekin in its non-prototypical sense to refer to an earlier time of events, i.e. ‘earlier, previously’ or ‘in advance’. The non-prototypical use of the adverbial priekin to refer to temporal scenes in discourse is determined by the speaker’s choice of the strategy and perspective of conceptualising a specific temporal scene. When the speaker chooses the strategy of text-internal origo to refer to temporal relations in discourse, the adverbial priekin is more suitable. The strategy of text-internal origo is chosen under the following conditions: a) the time of the story is the past; b) the story consists of at least two events. Nevertheless, the choice of conceptualising space and time depends on the conceptual capabilities of a specific speaker and his/her encyclopaedic knowledge.Since examples of the temporal use of the adverbial priekin have been detected in other subdialects apart from Lithuanian ones such as Slavic (Russian and Byelorussian) and in some Romance languages (French and Italian), it can be assumed that such realisation of temporal scenes in discourse could typologically be a common feature of these languages.
Keywords: Vilniškiai subdialect of Northeastern Aukštaitija; adverbial; priekin (‘ahead’, ‘frontward’); referential and cognitive semantics; conceptualising; text-internal origo; text-external origo; linguistic typology; Slavic language; Romance languages